Primary progressive aphasia patients evaluated using diffusion tensor imaging and voxel based volumetry-preliminary results - Fábio Pascotto de Oliveira; Jaderson Costa da Costa; Sabine Possa Marroni; Ana Maria Marques da Silva; Sthefanie Hansen Barreiro; Fábio Kunihiro Maeda; Mirna Wetters Portuguez (Arquivos de Neuro-Psiquiatria)
There are individuals who have a progressive language deficit without presenting cognitive deficits in other areas. One of the diseases related to this presentation is primary progressive aphasia (PPA). OBJECTIVE: Identify by means of diffusion tensor imaging (DTI) and measurements of cortical volume, brain areas that lead to dysphasia when presenting signs of impaired connectivity or reduced volume. METHOD: Four patients with PPA were evaluated using DTI, and measurements of cortical volumes in temporal areas. These patients were compared with two normal volunteers. RESULTS: There is a trend to a difference in the number and volume of related fibers between control group and patients with PPA. Comparing cortical volumes in temporal areas between groups yielded a trend to a smaller volume in PPA patients. CONCLUSION: Patients with PPA have a trend to impairment in cortical and subcortical levels regarding relevant areas.